Effects of CYP3A4*22 polymorphism on trough concentration of tacrolimus in kidney transplantation: a systematic review and meta-analysis - Kim, Jung Sun; Shim, Sunyoung; Yee, Jeong; Choi, Kyung Hee; Gwak, Hye Sun (Frontiers in Pharmacology, 2023)
Purpose: Tacrolimus (Tac) is a widely used immunosuppressive agent in kidney transplantation.Cytochrome P450 (CYP), especially CYP3A4 enzymes are responsible for the metabolism of drugs.However, the correlation between plasma Tac concentration and CYP3A4*22 gene variants is controversial. This meta-analysis aims to evaluate the association between CYP3A4*22 polymorphism and the dose-adjusted trough concentration (C0/D) of Tac in adult kidney transplant patients.Methods: We conducted a literature review for qualifying studies using the PubMed, Web of Science, and Embase databases until April 2022. For the continuous variables (C0/D and daily dose), mean difference (MD) and corresponding 95% confidence intervals (CIs) were calculated to evaluate the association between the CYP3A4 * 22 and Tac pharmacokinetics. We performed an additional analysis on the relationship of CYP3A5*3 with Tac PKs and analyzed the effects of CYP3A4*22 in CYP3A5 non-expressers.Results: Overall, eight eligible studies with 2,683 renal transplant recipients were included in this metaanalysis. The CYP3A4*22 allele was significantly associated with a higher C0/D (MD 0.57 ng/mL/mg (95% CI: 0.28 to 0.86; P = 0.0001) and lower mean daily dose requirement (MD -2.02 mg/day, 95% CI:-2.55 to -1.50; P < 0.00001). An additional meta-analysis demonstrated that carrying the CYP3A5*3 polymorphism greatly impacted Tac blood concentration. From the result with CYP3A5 non-expressers, CYP3A4*22 showed significant effects on the Tac C0/D and dose requirement even after adjusting the effect of CYP3A5*3.Patients with CYP3A4*22 allele showed significantly higher plasma C0/D of Tac and required lower daily dose to achieve the therapeutic trough level after kidney transplantation. These findings of our meta-analysis may provide further evidence for the effects of genetic polymorphism in CYP3A4 on the PKs of Tac, which will improve individualized treatment in a clinical setting.